Knowledge, attitudes and perceptions of Latin American healthcare workers relating to antibiotic stewardship and antibiotic use: a cross-sectional multi-country study - Bernan, Marisa Liliana (2024)
Background The burden of antimicrobial resistance (AMR) in Latin America is high. Little is known about healthcare workers’ (HCWs) knowledge, attitudes, and perceptions of antimicrobial stewardship (AS), AMR, and antibiotic use (AU) in the region. Methods HCWs from 42 hospitals from 5 Latin American countries were invited to take an electronic, voluntary, anonymous survey regarding knowledge, attitudes, and perceptions of AS, AMR, and AU between March–April 2023. Findings Overall, 996 HCWs completed the survey (52% physicians, 32% nurses, 11% pharmacists, 3% microbiologists, and 2% “other”). More than 90% of respondents indicated optimizing AU was a priority at their healthcare facility (HCF), 69% stated the importance of AS was communicated at their HCF, and 23% were unfamiliar with the term “antibiotic stewardship”. Most (> 95%) respondents acknowledged that appropriate AU can reduce AMR; however, few thought AU (< 30%) or AMR (< 50%) were a problem in their HCF. Lack of access to antibiogram and to locally endorsed guidelines was reported by 51% and 34% of HCWs, respectively. Among prescribers, 53% did not consider non-physicians’ opinions to make antibiotic-related decisions, 22% reported not receiving education on how to select antibiotics based on culture results and 60% stated patients and families influence their antibiotic decisions. Conclusions Although HCWs perceived improving AU as a priority, they did not perceive AU or AMR as a problem in their HCF. AS opportunities include improved access to guidelines, access to AMR/AU data, teamwork, and education on AS for HCWs and patients and families.